The regional dimensions of the european integration under the expected expansion of the European Union - Trifon Kostopoulos (European Regional Science Association (ERSA), 2002)
In this paper it will be made an attempt for a comparative political and economy evaluation of the European Integration with the criterion of regional inequalities of the european Union. The problem of the European Integration will be analyzed on the basis of national and regional inequalities of the European Union. Initially we will examine the regional dimension of the European unification on the asis of the European Union with 15 member-states (EU15). As criteria we select the different levels of economic development of the member-states examining the regional inequalities at national level. On this basis we obsserve that the member states converge creating the "hard core of Europe" and the member states diverge from the average level of the development of the European Union so that determining the countries of "community cohesion". Next we apply the previous criteria to the EU27,in other words it is useful to research the inequalities of the levels of economic development,which rrresult in the European Union,if all the others candidate countries would be able to be taken within the EI of 15 as is today. In the EU of 27 with the basis of per capita GNP exist three groups of countries instead of two as exist today. The first group it consists of the present member-states of the EU15,except Spain,Greece and Portugal of which the GNP per capita exceeds by 20% the new weighted average of the EU27. The second group it consists of the present member states of community cohesion, i.e. Spain Greece and Portugal plus Cyprus,Czechia, and Malta with percapita GNP between 68%(Czechia) and 95% (Spain) of the average of the EU27. The third group it consists of the remaining eight (8) candidate countries with GNP per capita below of the 40% of the average of the EU27, with the exemption of Slovakia and Hungary og which the GNP per capita lies between 56%-58% of the average of the EU27. Therefore, the expected expansion with the complex inequalities, will result a big challenge for the European regional policy, and the policy of the economic and social cohesion. First, the expansion will make more than double the population of the European Union that lives with GNP per capita below of the 75% of the present average of the EU.This number will raise from 71 million at the present to 174 million of people or different stated from 19% of the total of EU15 to 36% of the total of EU27. Second, the scale and the size of regional inequalities will be increased. Therefore, in the 1998 for the less developed regionsn the EU15 the per capita GNPwas an average of the EU15. With the expansion, the GNP per capita of the less developed regions of the candidata countries was on the 37% of the average of EU15. Therefore the co-existence of the poor and rich regions within the EU27 will make the regional inequalities more complex in this part of the Union which consists of poor countries. We may possibly will find ourselves in a new allocation of poverty. Finally, we will attempt to achieve the necessary interventions between the EU15 and the EU27, researching the modern problems of the EU under the expected expansion of the European Union.
Keywords: 330